Child Stunting in Parenting in Pinang Kencana Village, East Tanjungpinang - Chia Savitri; Nanik Rahmawati; Emmy Solina (Social Issues Quarterly, 2023)
This study focuses on the issue of child stunting in Pinang Kencana Village, East Tanjungpinang, Indonesia. One of the main causes of stunting is improper parenting due to a lack of knowledge regarding children's health patterns and weak parenting practices. In addition, there is a lack of supervision from health authorities which results in ineffective handling of stunting cases. The study employs a descriptive qualitative research method and uses Peter L. Berger and Thomas Luckman's theories to understand the social constructs surrounding stunting. The findings suggest that continuous efforts are needed to interpret and cultivate meaning in order to address the issue of stunting.